La jurisdicción voluntaria: una propuesta de nueva concepción, denominación y reordenación (Acta Judicial Journal, 2024)
The author of this article defends the lack of homogeneity of the regulation of this institution, as a consequence of not having discovered the adequate pattern of its structuring: the existence of legal unions. It is these and not the voluntariness of their actions, which determines their existence as an independent jurisdiction from the ordinary one. It also advocates a revitalization of the figure of the Lawyer of the Administration of Justice, to take charge of the full development of this jurisdictional function.
Keywords: jurisdiction, voluntary, unitary, discrepancies, divergences, controversies.